The BKPRMI Preaching Method in Shaping the Characters of Adolescents in the Bontomarannu Subdistrict - Irmawati Hasyim (Jurnal Mercusuar, 2023)
This research aims to examine the BKPRMI (Indonesian Islamic Propagation Institute) da'wah methods in shaping the character of teenagers in the Bontomarannu District and to assess the teenagers' response to BKPRMI da'wah methods in shaping their character in the same district. This study uses a qualitative descriptive research design conducted at the BKPRMI office in the Bontomarannu District, using management and sociology approaches. The primary data sources for this research are Kaharuddin Dg. Lallo, the Chairman of BKPRMI in the Bontomarannu District, as the key informant, and the Secretary of BKPRMI in the Bontomarannu District and the youth of the Bontomarannu District as additional informants. The secondary data sources include books, the internet, ebooks, journals, and complementary data sources. The data collection method involves several stages: observation, interviews, and documentation. Data analysis is carried out through three stages: data reduction, data presentation, and drawing conclusions. The results of this research indicate that BKPRMI in the Bontomarannu District has several da'wah programs, including "Safari Ramadhan" and "Bimbingan Remaja Masjid" (Guidance for Mosque Youth). Safari Ramadhan is used as a means of fostering friendship among fellow Muslims and increasing Islamic insights. During the Safari Ramadhan, BKPRMI officials provide advice, teachings, and Islamic guidance to the community and teenagers in the Bontomarannu District. "Bimbingan Remaja Masjid" is an effort by BKPRMI to shape the character of mosque youth by teaching discipline, responsibility, and initiative. BKPRMI officials in the Bontomarannu District provide guidance and direct instruction to mosque youth in villages and neighborhoods. In their da'wah implementation, BKPRMI in the Bontomarannu District adopts the method of "dakwah mau'izhah hasanah," which involves providing good advice, teachings, and guidance to the community and teenagers. BKPRMI officials also demonstrate the implementation of the "dakwah Al-Mujadalah" method, which involves discussing, debating, and arguing in a respectful and considerate manner with others. The implications of this research are that, after conducting research on the implementation of BKPRMI da'wah methods in shaping the character of teenagers, it is advisable for da'wah practitioners (dai) to conduct serious training to produce more qualified preachers. Furthermore, after teenagers participate in BKPRMI's study, they should focus more on the materials delivered by BKPRMI preachers to improve their character.